Medidas Implícitas de Valores Humanos: Elaboração e Evidências de Validade - Athayde, Rebecca Alves Aguiar (2012)
Traditionally, human values have been measured by explicit forms of measurement, like self-report questionnaires. Nevertheless, it is known that these measures are susceptible to social desirability influence, which tends to mask and skew the results. One of the forms that have been used to control this tendency is by the use of implicit measures, which presuppose a decrease in reactivity of the measurement. In this sense, considering the problems inherent in explicit forms of measurement and the lack of instruments in the area of implicit measures, particularly in regard of values, this study was designed, specifically, to focus on the Functionalist Theory of Human Values (Gouveia, 2003). This study aimed to: construct two measures of human values, based on an adaptation of the IAT (SC-IAT), versions pencil and paper (study 1) and computed (study 2). As specific objectives, we sought to test the structure of the Functionalist Theory of Human Values through implicit measures and correlate them with explicit measurement instruments. Participated in the study 1, 154 college students, which are predominantly women (70%) with an average age of 38 years (sd = 6.75). A Multivariate Analysis of Variance for repeated measures revealed differences between the scores in the congruent and incongruent tasks, thereby indicating the effect implicit in the association. Analysis of Multidimensional Scaling (MDS) Confirmatory revealed consistency between the theoretical model and the observed structure (Phi Tucker > 0.90), identifying the values belonging to each of the six sub-functions, which are structured by reason of the dimensions: kind of guidance and type of motivator. Through correlation analysis, we observed a low convergent validity between the SC-IAT-Values and the QVB. Furthermore, was observed the discriminating validity of the instrument within the social desirability scale. Moreover, no correlations were observed between the measured implicit and behavioral variable. The second study, with the participation of 50 students, which are predominantly women (54%) with a average age of 24.8 years (sd = 9.88). Through D score was observed on the implicit effect association. MDS analyzes revealed consistency between the theoretical model and the observed structure (Phi Tucker > 0.90) as well as computed. Through correlation analysis, can t to be observed the convergent validity of the measure with the QVB, however, it presented discriminating validity with the scale of social desirability. Again, no relationship was observed between the measured implicit and behavioral variable. In short, this dissertation has achieved its objectives, building the measure of human values implicit in version pencil and paper and computerized, testing the Functionalist Theory through this, as well as linking it with the explicit measures.